2016
DOI: 10.1038/aps.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates high glucose-induced podocyte apoptosis by regulating functional connections between caveolin-1 phosphorylation and ROS

Abstract: Aim: Caveolin-1 (cav-1) is a major multifunctional scaffolding protein of caveolae. Cav-1 is primarily expressed in mesangial cells, renal proximal tubule cells and podocytes in kidneys. Recent evidence shows that the functional connections between cav-1 and ROS play a key role in many diseases. In this study we investigated whether regulating the functional connections between cav-1 and ROS in kidneys contributed to the beneficial effects of curcumin in treating diabetic nephropathy in vitro and in vivo. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…In this study, we found that citral inhibits high glucose induced ROS production in the HepG2 cells [Table/ Fig-2]. It has been previously reported that curcumin, an active phytochemical effectively attenuated high glucose induced oxdative damage through inhibiting ROS generation in cultured mouse podocytes [31].…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we found that citral inhibits high glucose induced ROS production in the HepG2 cells [Table/ Fig-2]. It has been previously reported that curcumin, an active phytochemical effectively attenuated high glucose induced oxdative damage through inhibiting ROS generation in cultured mouse podocytes [31].…”
Section: Discussionmentioning
confidence: 72%
“…Unbalanced apoptotic cell death leads to renal cell loss and has been observed in podocytes, tubular cells, and endothelial cells in experimental diabetic nephropathy [8]. Diabetic nephropathy is the most frequent cause of end-stage renal disease in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress occurs when ROS affect the balance between oxidative pressure and antioxidant defense (23). SOD is an enzymatic scavenger of ROS, which can com bat the accumulation of ROS and limit oxidative injury (24).…”
Section: Overexpressed Mir-130a-3p/301a-3p Inhibited Hg-induced Mpc5 mentioning
confidence: 99%